A Redox‐Active Electrochemical Decoder. Issue 4 (31st January 2018) - Gaikwad, Pramod; Misal, Mahavir; Khaire, Siddhi; Raafik, Abdul; Aralekallu, Shambhulinga; Varhade, Swapnil; Bhat, Zahid Manzoor; Kottaichamy, Alagar Raja; Devendrachari, Mruthyunjayachari Chattanahalli; Gautam, Manu; Thotiyl, Musthafa Ottakam
Abstract: In communication systems, transmission of data between different locations requires encoders for encryption and decoders for decrypting encoded data. In modern digital devices, these functions are performed by transistors from their distinct logic levels. It is demonstrated that a redox‐active interface with twin interfacial states can decrypt encoded information through electrochemical means; consequently, it can function as an electrochemical decoder in memory devices. The redox‐active half‐cell electrode/electrolyte interface of the device furnishes bistable conducting and nonconducting states providing the logic HIGH and logic LOW levels of operation, respectively. The logic HIGH level of operation is prompted by self‐charge injection into the redox‐active polymeric backbone which is confirmed by quartz crystal microbalance, galvanostatic intermittent titration technique, and spectroelectrochemistry. A single cathodic interface allows bistable interfacial chemistry; consequently, 'n' cell combination can process second possibilities demonstrating the power of electrochemical interface in decoding encoded information. Abstract : A redox‐Active Electrochemical Decoder showing logic HIGH level and logic LOW level is presented. M1 is a metallic aluminum anode and P2 is a polypyrrole cathode immersed in acidic solution. A, B, C, D represent four different cells and μC the Microcontroller.